Investigating the effects of basil (Ocimum basilicum L.)c mucilage and cellulose nanofiber-based edible films with post-probiotics on fish fillet shelf life - Leila Mokhtaran; Sahar Sabahi; Mohammad Noshad; Seyyed Mohammad Ali Noori (Applied Food Research)
Fish is highly valued for its nutritional benefits, and health experts recommend consuming it at least twice a week. Among various types, salmon offers a cost-effective option; however, its perishable nature—even when refrigerated—creates conditions conducive to microbial growth, making the preservation of its quality and safety essential. This study aims to investigate the effects of an edible film composed of basil mucilage, cellulose nanofiber, and postbiotics on the shelf life of fish fillets, proposing it as a protective coating alternative to chemical preservatives. In this research, basil seed mucilage fortified with fiber nanocellulose and postbiotics of Limosilactobacillus fermentum was incorporated at concentrations of 0.5 %, 1 %, and 1.5 % to create a coating film for salmon fillets. The physicochemical properties of the film were examined, and the pH, moisture content, oxidation levels, sensory attributes, and microbial characteristics of the coated fish fillets were analyzed throughout a 12-day shelf life, with assessments conducted on days 0, 4, 8, and 12. The minimum thickness was observed in the basil seed mucilage sample, measuring 0.081 ± 0.01 mm, while the maximum thickness was recorded for the Basil seed mucilage+cellulose nanofiber+1.5 % postbiotic sample at 0.164 ± 0.01 mm. Additionally, the film with 0.5 % postbiotic showed the lowest water vapor permeability. Among the evaluated fish characteristics, control samples displayed the highest pH, moisture, total nitrogen compounds, and levels of peroxide and thiobarbituric acid. In contrast, fish fillets coated with the basil seed mucilage film, cellulose nanofiber, and 1.5 % postbiotic showed the lowest values for pH and thiobarbituric acid, while the sample with 1 % postbiotic exhibited the least moisture and volatile nitrogen compounds. The sensory evaluation revealed that the fish fillet sample coated with the basil seed mucilage film, cellulose nanofiber, and 1.5 % postbiotic received the highest score, comparable to the control sample. Microbial analysis indicated that the uncoated sample and the one with 1.5 % postbiotic showed the highest and lowest microbial counts, respectively, throughout the storage period. The sample featuring basil seed mucilage film, cellulose nanofiber, and 1.5 % postbiotic exhibited exceptional performance in maintaining the desirable qualities of fish fillets throughout the storage period, indicating significant potential for industrial application.